'More fronted adverbials than ever before'. Writing feedback practices and grammatical metalanguage in an English primary school. (2nd January 2019) - Hardman, William; Bell, Huw
Abstract: This case study investigates writing feedback practices and their relationship to the grammar, punctuation and spelling (GPS) objectives in the 2014 National Curriculum for England, with a particular focus on grammatical metalanguage. Our data is composed of authentic examples of children's writing in three classes at one primary school in the North-West of England over the course of almost a year. We investigate how primary-stage GPS objectives are reflected in the feedback practices of both children and teachers, and how children respond to this feedback. The findings indicate that, despite evidence of good feedback practice and useful knowledge of grammatical metalanguage among teachers and children, there is a tendency for feedback to be conducted at the surface level with a focus on metalinguistic features, sometimes at the expense of content-related concerns. We hypothesise that this is largely because of the focus on test preparation and the need to provide evidence of progress.